1994
DOI: 10.1038/ng0194-47
|View full text |Cite
|
Sign up to set email alerts
|

Three autosomal dominant corneal dystrophies map to chromosome 5q

Abstract: The two most common autosomal dominant dystrophies of the corneal stroma are lattice corneal dystrophy type I and granular dystrophy. A third autosomal dominant stromal dystrophy (Avellino) has also been recognized. Chromosome linkage analysis of four families with Avellino dystrophy mapped the disease-causing gene to chromosome 5q. Subsequent linkage analysis of two families with typical lattice dystrophy and two with typical granular dystrophy also revealed significant linkage with the same markers. Thus, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(59 citation statements)
references
References 27 publications
0
56
0
3
Order By: Relevance
“…Second, we applied this technology to the identification of susceptible loci co-segregated with CGD2 in a series of pedigrees by applying parametric linkage analysis. Parametric single-point and multipoint linkage analyses using the SNP genotypes confirmed linkage to TGFBI and provided LOD scores better than those obtained using microsatellites, as reported by Stone et al (Stone et al, 1994). In addition, we found a new locus on 3q26.3 (rs6445141) co-segregated with CGD2 in Korean families.…”
Section: Discussionmentioning
confidence: 55%
“…Second, we applied this technology to the identification of susceptible loci co-segregated with CGD2 in a series of pedigrees by applying parametric linkage analysis. Parametric single-point and multipoint linkage analyses using the SNP genotypes confirmed linkage to TGFBI and provided LOD scores better than those obtained using microsatellites, as reported by Stone et al (Stone et al, 1994). In addition, we found a new locus on 3q26.3 (rs6445141) co-segregated with CGD2 in Korean families.…”
Section: Discussionmentioning
confidence: 55%
“…1,2 Recent molecular analysis showed that different types of corneal dystrophies are caused by mutations in the transforming growth factor beta-induced gene (TGFBI), located on chromosome 5q31. [2][3][4] Several phenotypes are caused by specific mutations in the TGFBI gene such as: lattice corneal dystrophy type I (CDL1, OMIM122200), lattice corneal dystrophy type IIIA (LCDIIIA), granular corneal dystrophy (CDGG1, OMIM 121900), Avellino corneal dystrophy (ACD, OMIM 121900), Reis-Bü cklers's corneal dystrophy (CDRB, OMIM 121900), and Thiel-Behnke corneal dystrophy (CDB2, OMIM 602082). 1,4,5 Keratoepithelin, the protein product of the TGFBI gene, is an extracellular matrix protein expressed in many tissues including corneal epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…The genotypic approach contributes to the assessment and refinement of the diagnosis of corneal dystrophies particularly in the atypical cases. 2,4,5 Mutations in the TGFBI gene have been described in patients from many nationalities. [7][8][9][10][11][12] We report the first series of Brazilian patients screened for mutations in the TGFBI gene.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Missense mutations in BIGH3 gene in family members of these dystrophies mapping to 5q have been reported. 18 Mutations at codon 124 have been associated with LCD (arginine to cysteine).…”
Section: Commentmentioning
confidence: 99%